Rise and fall of Mexican Super Peso: Heterodox perspective versus orthodoxy - Laura Lisset Montiel-Orozco (Levy Economics Institute of Bard College, 2024)
This working paper contrasts the neo-Keynesian and post-Keynesian theories of monetary policy for an open economy, highlighting the irrelevance of the orthodox theory and the explanatory capacity of heterodoxy for an emerging economy such as Mexico. It focuses on the role of the central bank and the case of the Mexican currency during the economic recovery after the Great Lockout. In the first section, we criticize two proposals of the 3-Equation New-Keynesian model, concluding that, implicitly, both models reaffirm the extreme neutrality of money and the exchange rate in both the short and the long runs. In contrast, we analyze the post-Keynesian exchange rate model proposed by John T. Harvey (2009). In addition, we rely on the fundamentals of the heterodox school of thought such as the financial instability hypothesis of Hyman Minsky (1994) and the relevance of capital flows for the determination of the exchange rate and its implications for economic growth and prices by Jan Kregel (2008). Finally, the erratic behavior of the excessive appreciation of the Mexican Super Peso against the dollar after the recovery of the COVID-19 crisis and in the context of global risk is presented.
Keywords: E31; E52; E10; E12; F31; 330; Monetary Policy; New Keynesian Economics; post-Keynesian Economics; Foreign Exchange Rate; Mexico